Stoichiometry understanding of upper secondary students through active science learning - Wannomai, Manassawee; Nuangchalerm, Prasart; Islami, R. Ahmad Zaky El (Journal of Education and Learning (EduLearn), 2024)
The goals of the study were as follows: i) to design an active science learning activity on stoichiometry for grade 10 students, ii) to evaluate the academic achievement of grade 10 students after receiving an active science learning activity on stoichiometry, and iii) to investigate the perspectives of grade 10 students regarding an active science learning activity on stoichiometry. The research utilized a sample group consisting of 41 students who were enrolled in the tenth grade during the second semester of the academic year 2022. The research tools provided participants with active science learning lessons. A test of the kids’ academic prowess as well as their thoughts on the use of hands-on scientific learning activities will be administered. The mean, the standard deviation, and a one-sample t-test were the types of statistics that were utilized in the investigation. The following is an outline of what the research found: i) the appropriateness of the active science learning activities was judged to be the highest level, ii) the academic achievement of grade 10 students after receiving the active science learning activities on stoichiometry had an average score that was higher than the criteria of 70% with a statistical significance at the .05 level; and iii) the opinions of students on the implementation of active science learning activities on stoichiometry were in the agree level.